Water Supply and Sanitation in Rwanda : Turning Finance into Services for 2015 and Beyond - World Bank (World Bank, Nairobi, 2013)
Rwanda has made good progress in extending water supply and sanitation coverage during the past few years, under clear political commitment to three complementary sets of targets: the economic development and poverty reduction strategy (2012), millennium development goals (2015), and vision 2020. The report aims to help countries assess their own service delivery pathways for turning finance into water supply and sanitation services in each of four subsectors: rural and urban water supply, and rural and urban sanitation and hygiene. Rwanda is closing the gap on its targets, but is unlikely to attain the required coverage levels by 2015 without an increase in financing. The coverage trend over the past 10 years for rural water supply demonstrates the country's capacity for developing new projects; while for sanitation the enabling environment and capacity for service development will need to be strengthened further in the medium term. Households' capacity for sharing the costs of water supply capital investments is limited, and the strategy views their main contribution as being towards operations and maintenance costs, through water fees and tariffs. The rural water supply subsector has switched from a community management model, to one of public-private partnership. Nearly 30 percent of rural water schemes are already managed by private operators and the economic and poverty reduction strategy aims for 50 percent by 2012. This second African Ministers' Council on Water (AMCOW) Country Status Overview (CSO2) has been produced in collaboration with the Government of Rwanda and other stakeholders.